RESEARCH OF FACTORS AFFECTING THE CHOICE OF THE PROFESSION OF PHYSICAL THERAPIST - Ganna Ilnitska; Larysa Ilnitska; Liliya Ocheredko; Larysa Ulaeva; Victoria Spuziak ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The specialty "Physical therapy, ergotherapy" was chosen in almost equal gender ratio: women and men. Age category of students 17-21 years. Most enrolled after graduation, and a minority who had previously received specialized secondary education in medical schools and colleges. The most decisive in the choice of profession are the participants of the questioning called various factors. Priority factors most students consider "working conditions", the factor of higher education and prestige of the profession respectively; many respondents enjoy working with people, and the financial side (sallary) matters, more than half of respondents explained the choice of profession of physical therapist with insufficient number of qualified personnel in this field, slightly less than half of respondents chose a related profession with medical profession, and a minority entered the specialty on medical profession, parents' recommendation.